Effect of vortioxetine versus venlafaxine on cognitive functions in adults with major depressive disorder: A randomized-controlled trial - Chayan K. Manna; Rajeev Ranjan; Pankaj Kumar; Shamshad Ahmad; Santanu Nath (Indian Journal of Psychiatry)
Background: Vortioxetine and venlafaxine are antidepressants which have shown established efficacy to treat major depressive disorder (MDD). There are no studies that compared them for their efficacy in cognitive symptoms of depression. The study aimed to compare the effect of vortioxetine and venlafaxine on the change in cognitive scores in adults with MDD. Methods: The present study was an open-label, active-controlled parallel design randomized clinical trial. After randomization, baseline clinical evaluations by Montgomery–Asberg Depression Rating Scale (MADRS) and Social and Occupational Functioning Assessment Scale (SOFAS) were done and coding (subset of WAIS-IV), WCST, TMT, Stroop test, PGI memory were used to assess cognition in 100 unmedicated MDD patients. They were reassessed after eight weeks of monotherapy with vortioxetine or venlafaxine. Results: Primary cognitive measure (coding score) was found to be significantly higher (Mean Difference = 0.680; 95% CI:.202 to 1.158; P = 0.006) in vortioxetine in comparison with venlafaxine. Stroop test scores (word score, color score, color–word score) were also found to be significantly higher with vortioxetine. In other cognitive measures (WCST scores: total trials, total errors score, total perseverative responses score, total perseverative errors scores; TMT-A and B scores), a significant decrease in scores with vortioxetine in comparison with venlafaxine were observed. A significant decrease in MADRS and increase in SOFAS scores were observed with vortioxetine in comparison with venlafaxine. Both the drugs alleviated the symptoms of depression but vortioxetine was better tolerated. Conclusion: Our study findings suggest that improvement in cognitive scores is significantly higher with vortioxetine than venlafaxine over the eight weeks of monotherapy. Clinical Trial registration number: CTRI/2020/07/026819 (Registered with Clinical Trials Registry- India).